Studi Kelayakan Usaha Pretty Patty - FX Setiyo Wibowo; Michelle Zefanya; Mita Purnamasari; Dini Murniaty; Titus Indrajaya (Politeknik Sahid, 2026)
ABSTRACT Purpose: The purpose of this study is to analyze the feasibility study of Pretty Patty's food business from financial and non-financial aspects so that it can be decided whether it is feasible or not feasible to run in the future. Methods: Data collection techniques used are observation, interviews, and documentation. Furthermore, the data analysis method used is an analysis of financial aspects (IRR, NPV, BEP, PP, and Sensitivity analysis) and non-financial aspects (Technical and Technological aspects, Management and Legal, and Market aspects), as well as SWOT analysis using Strength-Opportunities (S-O). Implication: The results of this study indicate that Pretty Patty's business is feasible to run both from: 1) juridical aspects; 2) Technical aspects; 3) SWOT analysis; 4) Market and marketing aspects; 5) Management aspect; 6) Environmental aspects; 7) Financial aspects; and 8) financial aspect. Keywords: Business Feasibility, Food, Pretty Patty. ABSTRAK Tujuan: Tujuan studi ini untuk menganalisis studi kelayakan bisnis usaha makanan Pretty Patty dari aspek keuangan dan non keuangan sehingga dapat diputuskan apakah layak atau tidak layak untuk dijalankan ke depannya. Metode: Teknik pengumpulan data yang digunakan adalah observasi, wawancara, serta dokumentasi. Selanjutnya metode analisis data yang digunakan adalah analisis dari aspek keuangan (IRR, NPV, BEP, PP, dan analisis Sensitivitas) dan aspek non keuangan (aspek Teknis dan Teknologi, Management dan Hukum, serta aspek Pasar), serta analisis SWOT menggunakan Strength-Opportunities (S-O). Implikasi: Hasil studi ini menunjukkan bahwa usaha Pretty Patty layak untuk dijalankan baik dilihat dari: 1) Aspek yuridis; 2) Aspek teknikal; 3) Analisis SWOT; 4) Aspek pasar dan pemasaran; 5) Aspek manajemen; 6) Aspek lingkungan; 7) Aspek keuangan; dan 8) Aspek finansial. Kata Kunci: Kelayakan Bisnis, Makanan, Pretty Patty.